Analisa Faktor-Faktor yang Mempengaruhi Kepuasan Dealer Terhadap Loyalitas Para Dealer PT. Dwi Putera Jaya - Santoni dan Mukti Rahardjo (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this study is to find out 1) whether there is an effect of product quality on loyalty 2) whether there is an effect of price on loyalty 3) whether there is a cashback effect on loyalty 4) is there an effect of ontime payment bonus on loyalty. The population in this study were dealers of PT. Dwi Putera Jaya. The sample used in this study was 40 respondents. The sampling technique used was nonprobability sample with purposive sampling method. Overall the results of this study are 1) Product quality has a significant effect on loyalty, 2) Price has a significant effect on loyalty, 3) Cashback has a significant effect on loyalty, 4) Bonus Ontime Payment has a significant effect on loyalty.